Coalworkers' simple pneumoconiosis and exposure to dust at 10 British coalmines. Issue 2 (May 1982) - Hurley, J F; Burns, J; Copland, L; Dodgson, J; Jacobsen, M
Abstract : Five physicians' radiological assessments of coalworkers' simple pneumoconiosis (CWP) in 2600 coalminers at 10 British collieries have been studied in relation to the individuals' estimated lifetime (mean 33 years) exposure to respirable coalmine dust. Estimates of exposure were based on 20 years of observations at each colliery. Radiographic classifications were clearly associated with the measures of dust exposure. Important unexplained differences between some of the collieries were disclosed. Among men with similar cumulative dust exposures those with longer exposure time had higher prevalence of CWP. In general there was no evidence that the quartz concentrations experienced (average 5% of mixed dust) affected the probability of developing coalworkers' simple pneumoconiosis. Some men reacted unfavourably (two or more steps of change on the 12-point radiological scale) over a 10-year period to coalmine dust with a relatively high quartz content.